Kajian Teknis dan Ekonomis Penimbunan Sump MT4 Sebagai Upaya Optimasi Biaya Penambangan TAL Barat 2018 di PT. Bukit Asam Tbk Unit Pertambangan Tanjung Enim Sumatera Selatan - Rifki Aditya; Murad Murad (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. Tambang Air Laya (TAL) has two pits that are operating in 2018 is the W est TAL Pit and the Lingkar Pit. In W est TAL Pit there is MT4 sump which is a gathering place for water that enters the current Pit. In the W est TAL sump location there still are reserves that have not been taken due to the presence of lubrications. In January 2018, TAL Backfilling that placed on east side of MT4 sump has an indication of fracture. To overcome this situation it is necessary to cover up MT4 sump to prevent the avalanche of Backfilling TAL which will affect W est TAL mining process. The purpose of this research is to obtain the right embankment design based on technical aspects and to carry out economic analysis of the activities of W est TAL sump. Based on the results of the research carried out, the following points can be concluded. First, the most appropriate embankment design based on technical aspects is 6 meters high of slope, berm 30 meters, single slope 18 degrees, overall slope is 8-9 degrees and obtained a capacity of embankment 4,500,000 ccm. Then, coal reserves getting decreased to 357,730 tons due to hoarding in MT4 sump W et TAL. Third, there is no loss due to coal reserve loss thanks to the cost of extracting coal is much bigger in Rp. 14,784,395,827 than the total sales price of coal and there is a potential profit obtained by the accumulation of MT4 sump W est TAL at Rp. 192,354,742,470.   Keywords:  mine plan, optimization, mine design, economist, coal